2018
DOI: 10.1590/s0100-204x2018000600010
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous selection for yield, stability, and adaptability of carioca and black beans

Abstract: The objective of this work was to determine the efficiency of a simultaneous selection for yield, stability, and adaptability of bean genotypes of the carioca and black groups. In the 2016 harvest, two experiments were carried out in the state of Pernambuco, Brazil: one for the carioca group, with 20 genotypes, in the municipalities of Caruaru, Arcoverde, and Belém de São Francisco; and the other for the black group, with 12 genotypes, in the municipalities of Caruaru and Arcoverde. The parameters were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…For 100 seed weight, the CV ranged from 2.2 to 6.2%, and the SA ranged from 0.89 to 0.98, considered very high. These estimates indicated good experimental precision for the two traits and they are similar to those reported by Chiorato et al (2015) and Santos et al (2018).…”
Section: Resultssupporting
confidence: 86%
“…For 100 seed weight, the CV ranged from 2.2 to 6.2%, and the SA ranged from 0.89 to 0.98, considered very high. These estimates indicated good experimental precision for the two traits and they are similar to those reported by Chiorato et al (2015) and Santos et al (2018).…”
Section: Resultssupporting
confidence: 86%
“…Besides the environmental effects, reduced heritability may be associated with the nature of the character and the low genetic variability of the study population (RAMALHO et al, 1993;TORRES FILHO et al, 2017), observed low heritability (0.4) when evaluating cowpea strains for immature grain yield under environmental and soil conditions in Mossoró-RN. SANTOS et al (2018), obtained similar heritability when evaluating the adaptability and stability of common bean genotypes for grain yield in environments of the state of Pernambuco, using the methodology (REML/BLUP).…”
Section: Resultsmentioning
confidence: 83%
“…These results indicate that the genotypes of the early Carioca bean group differed genetically for grain yield potential and presented a different response to the environments where they were evaluated. This could be performed by the analyses of adaptability and stability, considering that edaphoclimatic factors have the greatest effect on the adaptability and stability of genotypes (TORRES et al, 2015;SANTOS et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It also generates results in the unit itself or the scale of the trait evaluated, which may be directly interpreted as breeding values that are not allowed by other methods. This model also allows additional inferences, such as the selection of specific genotypes for each environment; selection of stable genotypes (high predictability) in different environments and years; selection of genotypes (high adaptability) responsive (high adaptability) to the improvement of the environment; and simultaneous selection for yield, stability, and adaptability (CARVALHO et al, 2016;GONÇALVES et al, 2014;SANTOS et al, 2017;SANTOS et al, 2018;SANTOS et al, 2019;SOUZA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%